2008
DOI: 10.1152/ajpcell.90654.2007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of H2O2-induced necrosis by PKC and AMP-activated kinase signaling in primary cultured hepatocytes

Abstract: Recent studies have suggested that, in certain cases, necrosis, like apoptosis, may be programmed, involving the activation and inhibition of many signaling pathways. In this study, we examined whether necrosis induced by H2O2 is regulated by signaling pathways in primary hepatocytes. A detailed time course revealed that H2O2 treated to hepatocytes is consumed within minutes, but hepatocytes undergo necrosis several hours later. Thus, H2O2 treatment induces a “lag phase” where signaling changes occur, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 64 publications
6
46
0
Order By: Relevance
“…H 2 O 2 did activate neither JNK nor caspases and induced necrosis in rat hepatocytes (11). A similar observation was recently made in mouse hepatocytes (53). However, H 2 O 2 -induced necrosis involved JNK activation and was dependent on protein kinase C (53).…”
supporting
confidence: 68%
“…H 2 O 2 did activate neither JNK nor caspases and induced necrosis in rat hepatocytes (11). A similar observation was recently made in mouse hepatocytes (53). However, H 2 O 2 -induced necrosis involved JNK activation and was dependent on protein kinase C (53).…”
supporting
confidence: 68%
“…PKC stimulation inhibits the apoptosis of different types of cells (38)(39)(40). Meanwhile, PKC also participates in the protection against hepatic ischemia reperfusion injury and is involved in the processes of cellular proliferation and apoptosis (19,41). We observed that despite δ-opioid receptor activation, the blockade of the PKC pathway increases the apoptosis of human liver cells.…”
Section: Discussionmentioning
confidence: 75%
“…Studies have found that PKC is involved in the preconditioning protection of hepatic ischemia (18). The proliferation and apoptosis of normal cells and hepatic tumor cells closely correlate with PKC (19)(20)(21)(22). Recent findings have shown that opioid receptors share a common pathway with the phosphorylation of PKC.…”
Section: Activation Of the δ-Opioid Receptor Inhibits Serum Deprivatimentioning
confidence: 99%
“…5,14 Necrosis has been described as a consequence of physical and chemical stress, which is passive and accidental. However, recent literature argues that necrosis is a result of a well-orchestrated interplay of signalling cascades, 27 with an extensive crosstalk between biochemical and molecular events. 28,29 Furthermore, some signalling molecules, which play a role in autophagy and apoptosis, also take part in this interplay.…”
Section: Dynamics Within Modes Of Cell Deathmentioning
confidence: 99%